Commonwealth SIDS and UK Overseas Territories sustainable fisheries programmes: An overview of projects and benefits of official development assistance funding. (September 2019) - McManus, Edmund; Collins, Martin; Yates, Oliver; Sanders, Matthew; Townhill, Bryony; Mangi, Stephen; Tyllianakis, Emmanouil
Abstract: In recent years, Official Development Assistance (ODA) funding has decreased for sustainable fisheries projects worldwide. However, the UK Government has committed to ringfencing 0.7% GDP to international development assistance to support a large range of programmes worldwide including, where appropriate, sustainable fisheries and aquaculture capacity building in Overseas Territories and the Commonwealth. This is with the aim of reducing poverty, increasing resilience in the fisheries sector to climate change impacts and increasing food security. The primary objective of this paper is to demonstrate the significant support by UK Government to the Commonwealth Small Island Developing States (SIDS) and UK Overseas Territories (OT) and the impacts of such interventions. This support is illustrated through an introduction to the Commonwealth Marine Economies programme and the Blue Belt programme. In this paper the emerging trends for ODA support are set out, then the importance of fisheries to a selection of ODA-eligible states is highlighted. Finally, illustrative examples of projects from two key UK Government programmes in Commonwealth states and UK Overseas Territories that demonstrate a wide range of potential capacity building support activities and derived benefits to the states are summarised. We explain how activities to sustainably develop the fisheries sector in Commonwealth Small Island Developing States (SIDS) and UK Overseas Territories (OT) enhance biodiversity protection and create opportunities to support 'Blue Growth' (the long-term strategy to support sustainable growth in the marine sectors).